Information, incentives, and education policy - Neal, Derek A. (Sanford J. Grossman lectures in economics series, 2018)
Derek Neal writes that economists must analyze public education policy in the same way they analyze other procurement problems. He shows how standard tools from economics research speak directly to issues in education. For mastering the models and tools that economists of education should use in their work, there is no better resource available-- Provided by publisher.